Author Correction: Ultrafast switch-on dynamics of frequency-tuneable semiconductor lasers. Issue 1 (December 2018) - Kundu, Iman; Wang, Feihu; Qi, Xiaoqiong; Nong, Hanond; Dean, Paul; Freeman, Joshua; Valavanis, Alexander; Agnew, Gary; Grier, Andrew; Taimre, Thomas; Li, Lianhe; Indjin, Dragan; et al.
The original version of this Article contained an error in the Acknowledgements, which incorrectly omitted the following: 'We also acknowledge support from the Australian Research Council's Discovery Projects Funding Scheme (Grant DP 160 103910).' This has been corrected in both the PDF and HTML versions of the Article.